Implementasi Sistem Penunjang Keputusan Dalam Pemilihan Calon Team Leader Menggunakan Metode Simple Additive Weighting (SAW) - Purba, Ade Rizki Sariaman; Kusumaningsih, Dewi (Jurnal Informatika Universitas Pamulang, 2020)
So far, the selection of prospective Team Leaders in companies is still manual so it is not in accordance with the standard operating procedures for selection. The system designed in this study aims to ensure the accuracy of HRD in selecting candidates Team Leader to match the expectations of the company itself. From the comparison of the methods that have been carried out by researchers, themethod is the Simple Additive Weighting (SAW)right choice and the researcher will implement it with the provisions of the criteria that have been set including, Communication,Â  Problem Solving Skills, Time Management, English, Achievement. To build this system, researchers used the programming languages PHP and MySQL. From the calculation of the level of accuracy, manual calculations get a percentage of 86.6% while the calculation with the proposed system achieves the maximum result with a percentage of 100%. It can be concluded that the calculation with the system is able to determine a suitable candidate as a Team Leader very accurately and on target.